292 FACTORS AFFECTING HEALTH CARE PROVIDER CHOICE IN SIEM REAP, CAMBODIA. (1st January 2006) - Schmitz, B.; Sakhem, N.; Bezruchka, S.; Morgan, M. S.
Abstract : Purpose: The Capacity Building and Heath Education Program (CBHEP) is an NGO working in conjunction with the Cambodian Ministry of Health to improve the capacity and the quality of community health services and the public health infrastructure in and around Siem Reap, Cambodia. One of CBHEP's major projects is focused on capacity building in local area health centers (government-funded, free, primary care clinics). CBHEP would like to assess the factors determining provider choice, as well as to get descriptive data for those living in the service area of the Prasat Bakong Health Center. Study Design and Methods: A cross-sectional survey was orally administered, in Cambodian, following verbally administered oral consent. The survey was administered to 102 families in 17 different villages served by the Prasat Bakong Health Center. Sixteen Village Health Volunteers (VHVs), trained by the PI and CBHEP, served as survey administrators. Six families were randomly selected from each village. Survey questions dealt with attitudes about/awareness of different health care options available, past and future health-seeking behaviors and practices, provider utilization, as well as socioeconomic factors such as family size, income, profession, etc. Results: After analyzing the data the most powerful predictor of provider choice is the age of the patient to be treated. When subjects were asked where they would take a family member to receive treatment for a broken bone, the majority chose home care for a patient over the age of 50 (51.4%), hospitalization for a patient under 18 (86%), and traditional medicine for a patient between 18 and 50 (59.2%), with a chi-square value of 157.13 ( p ≤ .001). Similar results were obtained for a similar item concerning patients experiencing diarrhea for > 1 week: chi square: 103.48 ( p ≤ .001), with hospitalization again as the first choice for those under 18. Other factors such as income level, literacy, and education did not correlate significantly with provider choice. Conclusion: Based on these data, the most reliable predictor of health care provider choice is the age of the patient to be treated, with a tendency to utilize hospitalization (tertiary level care) as a first option for those under age 18. These findings imply that the subjects have very precise ideas about what type of health care provider to utilize based on what generation the patient belongs to in the family. Other factors such as income, literacy, and education did not correlate with provider choice.